Effectiveness of the Maternal and Child Health handbook in Burundi for increasing notification of birth at health facilities and postnatal care uptake. Issue 1 (1st January 2017) - Kaneko, Kayo; Niyonkuru, Jacques; Juma, Ndereye; Mbonabuca, Térence; Osaki, Keiko; Aoyama, Atsuko
ABSTRACT: Background : In Burundi, birth certificate ownership (56.4%) and postnatal care (PNC) coverage (30%) remain low. Birth certificates prove birth registration and allow clients to receive free medical care including PNC. To obtain birth certificates, notification of birth by witnesses is indispensable. However, use of existing parallel home-based records for mother and child has prevented clients from successfully receiving notification of birth and related information. Objective : To assess the effectiveness of the Maternal and Child Health (MCH) handbook for increasing notification of birth at health facilities and PNC uptake. Methods : Pre- and post-introduction measurement were applied including: (i) structured interviews with two different sets of randomly selected mothers having infants aged less than six weeks at the pre- or post-studies; and (ii) secondary data from the national health management information system. Results : 95.1% of mothers had an MCH handbook post-study. Significant improvement was observed in the proportion of mothers receiving notification of birth at health facilities, from 4.6% to 61.0% (95% confidence interval [CI]: 55.9%–66.2%), and the proportion of mothers receiving guidance on PNC, from 35.9% to 64.2% (95% CI: 59.2%–69.3%). The annual PNC coverage (43.9% to 54.2%; p < 0.05) in the Gitega District significantly increased from 2013 to 2014. Among MCH handbook owners, mothers giving birth at hospitals/clinics had 2.62 higher odds (95% CI: 1.63–4.22) of obtaining notification of birth than mothers giving birth at health centers. Conversely, mothers delivering at hospitals/clinics had 0.51 lower odds (95% CI: 1.63–4.22) of receiving PNC guidance than mothers delivering at health centers. Conclusions : As previous studies showed, the MCH handbook appeared to help health personnel provide guidance on PNC, thereby it may have increased PNC. Furthermore, this study suggests the handbook contributed to every birth being counted. However, to increase the effectiveness of the handbook, health personnel should be encouraged toward its proper use.